Factors Enhancing English Speaking Ability: Perspectives from Thai High School Students and Their Teachers - Triwittayayon, Thanatchaporn; Sarobol, Nopporn (THAITESOL Journal, 2019)
Regarding the English language skills, speaking seems to be the most crucial skill in terms of communication or interaction in daily lives (Ur, 1996). This present study aimed to investigate factors enhancing English speaking ability, also the most influential factor affecting speaking ability. The participants were 5 high school students who had received awards from a national speech competition to guarantee their English speaking ability and 10 English teachers who had taught those students or trained them to participate in the competition. Semi- structured interview and in-depth interview were used as research instruments. The findings revealed that factors which enhanced the students to be fluent in speaking English were their language learning styles, age, attitudes, family support, personality, exposure to the language, and their English teachers, while personality and their exposure to the language were the most influential factors. The results of this study will benefit both teachers and students in regard to getting insight on the factors that may have an influence on the students’ English speaking ability.